Aromatic Fused [30] Heteroannulenes with NIR Absorption and NIR Emission: Synthesis, Characterization, and Excited‐State Dynamics. Issue 24 (25th April 2016) - Mallick, Abhijit; Oh, Juwon; Kim, Dongho; Rath, Harapriya
Abstract: Two hitherto unknown planar aromatic [30] fused heterocyclic macrocycles (1.1.0.1.1.0), with NIR absorption in free‐base form and protonation‐induced enhanced NIR emission, have been synthesized from easy to make precursors. The induced correspondence of fusion on the macrocyclic structure, electronic absorption, and emission spectra have been highlighted. Abstract : Two hitherto unknown planar aromatic [30] fused heteroannulenes (1.1.0.1.1.0) with near‐IR (NIR) absorption in free‐base form and protonation‐induced enhanced NIR emission are reported.